Enabling the language of accessible tourism. Issue 4 (3rd April 2018) - Gillovic, Brielle; McIntosh, Alison; Darcy, Simon; Cockburn-Wootten, Cheryl
ABSTRACT: The growing body of literature on "accessible tourism" lacks a critical scholarly debate around its specific language use and nomenclatures. To fill this gap, this paper provides a first examination of language. Language provides a unique capability to resist, strengthen and reframe identities of individuals and groups, yet can also reinforce, weaken and perpetuate dominant worldviews of disability. A content analysis examined previous accessible tourism literature with results illustrating that diversity exists amongst the varying terminologies adopted by scholars. Terms were employed loosely, inconsistently and interchangeably, euphemistically with erroneous understandings and nuances. The paper concludes with critical discussion about the power of researchers to (re) produce oppression through language that maligns and misrepresents, or to (re) conceptualise and (re) construct the world we live in with liberating language that facilitates positive social change.